The effect of the source of nitrogen on protein fractions and their proportions in barley grains - Ulla Lallukka; Eero Varis; Ritva Repo (Agricultural and Food Science, 1982)
The effects of fertilizer nitrogen, preceeding leguminous crop in rotation, and mixed cropping of barley with field beans on the protein fractions in mature barley grains were studied with the material collected from three experiment sites in southern Finland. With an increase in nitrogen application, the total N in grains as well as nitrogen in the different Osborne fractions increased. The relative amounts of protein fractions changed: prolamin increased, glutelin remained fairly constant, and salt-soluble fraction decreased. The preceeding leguminous crops, pea and field bean, increased the nitrogen content in barley as well as the proportion of prolamin N. The share of prolamin N in barley following leguminous plants was higher than in barley following oats, where the similar total N content was due to fertilizer nitrogen. In mixed cropping of barley and field beans prolamin N in harvested barley grains also increased with the increased total nitrogen due to an increase either in fertilizer application or in the share of field bean in the mixture. In this case there was no clear difference in the proportions of prolamin N between the treatments. The proportions of salt-soluble fractions were slightly higher and that of storage protein lower in Finnish barleys studied than in the results from other studies, where Central European cultivars with larger grains were used.